Riesgo país e inversión extranjera directa en el Perú, período: 2005 – 2019 - Sánchez Castañeda, María Ysabel (2021)
The country risk determines the probability that a state meets its financial obligations, it is also a reference indicator in investment decisions of foreign capital. Therefore, the main objective of this research is to determine the influence of country risk on foreign direct investment in Peru, during the period 2005 to 2019. A study was developed with a non-experimental, longitudinal, quantitative and relational design, using a model double logarithmic in which the variables that explain direct foreign investment were considered, including country risk, gross domestic product and market size based on quarterly time series. The results indicate that an increase in country risk has an inverse influence on foreign direct investment, while an increase in gross domestic product and market size have a direct influence on foreign direct investment.